Investigating the Relationship between Safety Climate and Safe Behavior in Arak Petrochemical Complex in 2018 - ezatollah heidari; samira ghiasi; masoud motlleby kashani (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: In order to improve the level of safety and control accidents in the workplaces, it is essential to check the level of safety and safe behavior. The purpose of this study was to evaluate the safety climate and safe behavior among the personnel of Arak petrochemical complex. Methods: This cross-sectional study was carried out at Arak Petrochemical Complex in 2018. All personnel of this complex (n = 122) were selected using the census method. In order to assess the safety climate and safe behavior, standard questionnaires were used. Data analysis was performed using the SPSS version 18. Results: Among the factors affecting on safety climate, adequacy of health and safety procedures and rules as well as personnel participation in safety and health issues were the highest and lowest scores, respectively. Furthermore, among the factors of safe behavior, participation and safety observance factors received 2.77 and 2.72 scores, respectively. In this study, education, competency, and production pressure factors had a significant relationship with age groups. Moreover, production pressure and violations of rules factors had a significant association with work experience. Education and competency factors were also significantly correlated with marital status. In addition, a significant relationship was found between all safety climate factors and the occupational groups. Discussion and Conclusion: Considering the significant statistical relationship between safety climate and safe behavior with occupational groups and demographic characteristics, more effective attention should be paid to workforce in the workplace.